2022
DOI: 10.20546/ijcmas.2022.1102.040
|View full text |Cite
|
Sign up to set email alerts
|

Phytochemical Evaluation and Uses of Ximenia americana L in Central Darfur

Abstract: Ximenia americana bark, leaves, and fruits which belong to the family Olacaceae traditionally used for the treatment of different human ailments. The study was conducted to evaluate the scientific basis for the use of the plant. Chemical constituents of the extract were also determined. The extract was active against different microbiological organisms were found. Phytochemical screening extract showed the presence of saponins, few alkaloids, tannins, flavonoids, terpenes, triterpenes sterols, and coumarins in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
4
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 0 publications
3
4
1
Order By: Relevance
“…In a similar study, alkaloids and saponins were detected while steroids were absent in aqueous and ethanol stem bark extract of X. americana. However, glycosides were detected in the ET extract, though absent in the AQ extract [26]. The present study agrees with this study as glycosides were detected only in the ET extract.…”
Section: Alkaloidssupporting
confidence: 92%
See 1 more Smart Citation
“…In a similar study, alkaloids and saponins were detected while steroids were absent in aqueous and ethanol stem bark extract of X. americana. However, glycosides were detected in the ET extract, though absent in the AQ extract [26]. The present study agrees with this study as glycosides were detected only in the ET extract.…”
Section: Alkaloidssupporting
confidence: 92%
“…GCMS analysis also indicated saturated (palmitic acid) and unsaturated (oleic acid) are present in both the AQ and ET extract of X. americana. These unsaturated (oleic) and saturated (palmitic acid) fatty acids were previously reported in a similar study on alcohol extract of X. americana [26]. In a previous study for GCMS analysis of X. americana in different solvent fractions, oleic acid and palmitic acid were detected in the highest amount in the chloroform fraction [38].…”
Section: Alkaloidssupporting
confidence: 68%
“…These variations could be explained by the temperatures of the oils but also by the extent of refining of the oils. Some authors such as Oladipo et al [20], and Sharief et al [10] who also worked on X. americana oils found refractive index values similar to ours (1.467 and 1.470). According to the ISO 6320-2017 standard, the values obtained in our study indicate a good purity of the oils.…”
Section: Physicochemical Parameterssupporting
confidence: 87%
“…As the oil has softening properties it can also be applied in crafts for better treatment of the leather [9]. Moreover, it was also found that oils from the almonds of X. americana contain high nutrients such as vitamins, protein, carbohydrates and particularly unsaturated fatty acids such as oleic and linoleic acid [10,11]. For that, the oil was recommended for nutritional use [10].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation